Study on neuromuscular manifestations in patients with diabetes mellitus - a study of 100 cases - Sardar, Md Hafiz; Hossain, Mohammad Murad; Hossain, Mohammad Zaid; Bari, Anwarul (Journal of Dhaka Medical College, 2015)
Background: There are common, important and various types of relationships between DM and NMM. The aim of this study was to find out patterns of NMM in diabetic patients and to find out a strategy to improve the outcome of the neuromuscular (NM) complications in patient with Diabetes Mellitus. Methods: The results were based on hospital based observational data from 100 consecutive patients, both men and women (aged e14 to 70 years) with diabetes with neuro-muscular (NM) manifestations. Patients were assessed by a meticulous history, relevant general and systemic examination and with the aid of NM Function Assessment, appropriate investigations and semi structured questionnaire. This study was done in Dhaka Medical College Hospital, Dhaka, from January to June of 2013. Results: Neuromuscular disorders are a common finding among patients with both type 1 and type 2 diabetes mellitus but more common in type 2. DM was associated with some of NMM. Among the100 diabetic patients who were screened, exhibit neuromuscular abnormalities, mainly various types of peripheral neuropathies and muscular abnormalities, like diabetic muscular infarction and diabetic amyotrophy. The association between widespread NMMs and DM was most evident among the group of individuals aged around 50 years with type 2 DM. Conclusion: In this hospital based observational study, NM abnormalities, mainly of the sensory-motor type of peripheral neuropathy and few cases of muscular abnormalities are found. The information thus gathered may provide useful guidelines for diabetic patients with neuromuscular manifestations &thus sufferings of the patients can be reduced. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22700 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 84-88